Effects of Konjac Glucomannan and Its Oligosaccharides on Improvement of Lactose Intolerance as Gut Prebiotics - Deng, Liling; Zhong, Geng; Zhang, Dongxia; Zhu, Zhaojing; Peng, Yongbo (ACS omega, 2024)
Lactose intolerance (LI) is a widespread health issue affecting almost 70% of the world population. This study evaluates the potential prebiotic benefits of konjac glucomannan (KGM) and konjac oligogalactomannan (KOGM) in improving LI. Colonic fermentation results indicate that lactase groups of healthy subjects showed lower pH, higher lactic acid content, and lactase activity in fermentation broth compared with LI subjects. Total short-chain fatty acid (SCFAs) content reached 1.71 mmol/L in healthy subjects, whereas it was 1.49 mmol/L in LI subjects. In vivo studies demonstrated that KGM and KOGM intake reduced total cholesterol (T-CHO) and triglyceride (TG) levels in the liver and significantly increased immunoglobulin G (lgG) and immunoglobulin A (lgA) values, while KOGM inclusion led to a significant 23.04% increase in serum free fatty acid (FFA) levels compared to the Blank group (p < 0.05). Furthermore, ileal tissue analysis revealed a marked increase in villus height and intestinal wall thickness (p < 0.05) as well as a decrease in crypt depth (p < 0.05). The composition and proportion of gut microbiota have improved with KGM and KOGM use, notably increasing the abundance of Lactobacillus and Lachnospiraceae_NK4A136_group, respectively (p < 0.05). Compared with the Blank group, Lactobacillus abundance increased by approximately 25.82% in the Drug group, 18.23% in the KGM group, and 8.67% in the KOGM group. These findings suggest that KGM and KOGM can be utilized as prebiotics to alleviate LI symptoms.